Ferromagnetic resonance in single vertices and 2D lattices macro-dipoles of elongated nanoelements: measurements and simulations. (11th November 2020) - Bang, Wonbae; Silvani, R; Hoffmann, A; Ketterson, J B; Montoncello, F; Jungfleisch, M B
Abstract: We report broadband ferromagnetic resonance measurements of the in-plane magnetic field response of three- and four-fold symmetric vertices formed by non-contacting permalloy nano-ellipses together with extended lattices constructed from them. Complementing the experimental data with simulations, we are able to show that, as far as the most intense FMR responses are concerned, the spectra of vertices and lattices can largely be interpreted in terms of a superposition of the underlying hysteretic responses of the individual ellipses, as elemental building blocks of the system. This property suggest that it is possible to understand the orientation of the individual magnetic dipole moments in a dipole network in terms of dynamic measurements alone, thereby offering a powerful tool to analyze the alignment statistics in frustrated systems that are exposed to various magnetic histories.